Analysis of Road Safety Conflicts. The Case Study of a Road Interchange in Guimarães, PT - Araújo, C. M. C. (2019)
This paper presents a case study to identify road safety conflicts in an interchange of the road network of the city of Guimarães, Portugal. For that an analysis using the SSAM (Surrogate safety assessment model) software was performed in order to identified and characterized the network points of conflict according their category and severity. To analyze traffic conflicts vehicles routes must be collected and inserted in SSAM software. To obtain vehicle routes a microsimulation traffic modelling was performed through the usage of PTV VISSIM software. Thus, a traffic and geometric data collection was done for the peak hour in the morning, and then the model was calibrated and validated using traffic volumes, travel time and queuing length using specific sections of the interchange. In addition, to identify and analyze three types of conflicts (rear end, lane change and crossings) with SSAM were evaluated two parameters the TTC (Time to Collision) and the PET (After Invasion Time) for all the vehicles, using their routes extracted from VISSIM. The location of the conflicts was analyzed in a GIS, which allowed the creation of maps of conflicts. The results shown that the most frequent conflicts are the rear end conflicts (1174), which occurs a little throughout the entire interchange and are more frequently in the entrances and exits of the freeway, which was also verified for lane change conflicts (107), but in a lower frequency. Based on these results it was also possible to conclude that the high number of conflicts should be a matter of concern for transport authorities, who may have to adopt measures to improve safety and reduce the potential for accidents, which may imply a reduction of speed in this interchange or a police reinforcement.